KAJIAN KERAGAAN TIGA VARIETAS KACANG TUNGGAK DAN KEBERADAAN RHIIZOBIUM INDIGEN DI LAHAN LEBAK KALIMANTAN SELATAN - Jamzuri Hadi (BUANA SAINS, 2008)
A field experiment had been conducted to study growth performance and yield of stick nut in tidal swamp land of South Kalimantan as well as to describe growth of Rhizobium colony and to obtain dominant indigenous Rhizobium isolate in the area. The experiment was conducted in shallow tidal swamp land of Hulu Sungai Selatan Regency and in middle tidal swamp land of Hulu Sungai Tengah Regency of South Kalimantan. Varieties of stick nut used for the study were Nagara local variety, high yielding varieties of KT-2 and KT5. The stick nut seeds were planted in a 4 x 3 m plot with planting distance of 75 cm x 50 cm. Measurements were stick nut performance, nodule distribution patterns and characteristics of indigenous Rhizobium. Results of this study showed that there were no significant differences in plant performance of the tree varieties in the two land types. However, diversity index of Rhizobium and nodule distribution patterns observed in the shallow tidal swamp land differed from those observed in middle tidal swamp land’. Three dominant Rhizobium isolates were found in the two land types